Integrated metabolomic and transcriptomic analyses elucidate anthocyanin-mediated flesh coloration mechanisms in red-fleshed pear - Du, Mengning; Wang, Yanan; Zhang, Xiangzhan; Wang, Suke; Su, Yanli; Wang, Long; Xue, Huabai (Frontiers in Plant Science, 2025)
The red-fleshed pears embody a unique and invaluable genetic resource. However, the specific types of metabolites in red-fleshed pears and its molecular mechanisms remain largely unknown. To understand these, targeted carotenoid and anthocyanin metabolomics as well as transcriptomics analyses were carried out in this study, using red-fleshed material ‘M2’ and white-fleshed material ‘XM’. The results showed that the concentrations and proportions of anthocyanins are the predominant determinants of the flesh coloration in red and white cultivars, rather than carotenoids. Notably, cyanidin-3-O-galactoside is the main anthocyanins enriched in red-fleshed pear ‘M2’. Moreover, a total of 6168 common differentially expressed genes (DEGs) between red and white flesh tissues were identified, KEGG and GO enrichment analyses showed that 42 DEGs were significantly enriched in the flavonoid and anthocyanin biosynthesis pathways. Correlation analysis of the transcriptome and metabolome revealed associations between core metabolites and genes, leading to the identification of several key transcription factors potentially involved in anthocyanin biosynthesis, such as PcWER, PcbHLH062, PcGSTF12, and PcMYB114. Overall, this study not only provides new insights into the color formation mechanism of red-fleshed pears but also provides guidance for further breeding of red-fleshed pears through the manipulation of anthocyanin biosynthesis.